EU economic governance: Less might work better than more - Karl Whelan (University College Dublin, UCD School of Economics, 2010)
The European Commission has recently proposed a new package of reforms of the Stability and Growth Pact. The package contains a number of good proposals. In particular, the increased focus on debt ratios is a very positive suggestion though this should be strengthened further. However, some of the other proposals, such as the new principle of prudent fiscal management and the scoreboard for non-fiscal imbalances, are poorly thought out and perhaps unworkable. A smaller number of well-focused proposals may end up working better than this complex, and perhaps overly ambitious, package. And a coherent policy to allow for orderly sovereign defaults in Euro area member states would probably place more pressure, via bond markets, on states to get their fiscal houses in order than would the proposed system of fines.
Keywords: 330